The Effect of Thawing Temperature on Sperm Quality of Friesian Holstein Bulls - Tri Utami; Tarsisius Considus Topianong (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2014)
The percentage of sperm motility and morphology are important criteria in evaluating the quality of sperm before it is used for artificial insemination (AI). This study was conducted to observe post thawing motility and abnormal morphology of spermatozoa Friesian Holstein (FH). The materials were used 10 straws of FH bulls in the form of 0.25 ml. A total of 10 straws then divided into two treatment groups of thawing in water at 37°C and water 8°C, respectively. An examination of the motility and morphology of spermatozoa abnormalities performed every two hours for two times. Calculating the percentage of sperm motility was done by calculating the percentage of spermatozoa moving forward in the field of view under a microscope with a magnification of 10x. the percentage of abnormal spermatozoa was assessed by William's stain. Spermatozoa morphology was observed by using a microscope magnification of 100x. Abnormalities of spermatozoa were calculated from a total of 200 spermatozoa, either normal or abnormal. At the same thawing time, the motility of FH cattle sperms post thawing in water temperature 37°C had a higher preference than that of post thawing in water temperature 8°C, although it was not significantly different (P > 0.05). Based on morphological aspects, frozen semen used in this study is within the tolerance limit for the total percentage of abnormal sperm morphology between 12% to 23% and normal morphology between 70% to 88%.